THE EFFECT OF STRUCTURED ASSIGNMENTS USING THE NUMBERED HEADS TOGETHER (NHT) COOPERATIVE LEARNING MODEL ON STUDENT LEARNING OUTCOMES AT STATE SENIOR HIGH SCHOOL 5, WEST SERAM - Amalia waleulu (PT. Jurnal Center Indonesia Publisher, 2025)
The purpose of this study was to describe how structured tasks from the Numbered Heads Together (NHT) cooperative learning model impacted the learning outcomes of grade X students at SMA Negeri 5 Seram Bagian Barat in the 2024–2025 academic year. This study was experimental and only used a control group for the posttest. This study involved 75 students from three classes at SMA Negeri 5 Seram Bagian Barat. Class X2 (experimental class), consisting of 25 students, and class X3 (control class) were included in the randomly selected sample. According to statistical analysis of the data, the control class obtained a score of 65.60 with a standard deviation of 13.25, while the experimental class obtained a score of 75.00 with a standard deviation of 10.40. The completeness of the experimental class was 84.00%, while the control class was 44.00%. Based on the results of the study, the structured task approach influenced the learning outcomes of grade X students of SMA Negeri 5 Seram Bagian Barat on the topic of chemical bonds.